Real-time parameter estimation of dynamic temperature models for greenhouse environmental control - Cunha, J. B. (2013)
For a greenhouse located at UTAD-University, the methods used to estimate (in real-time) the parameters of the inside air temperature model will be described. The structure and the parameters of the climate discrete-time dynamic model were previously identified using data acquired during two different periods of the year. Several experiments showed that the second-order models identified achieve a close agreement between simulated and experimental data. Later, it was found that parameters change with varying operational conditions. Thus, for an efficient use of these models in real-time control, a recu~ive identification technique was implemented for the estimation of the parameters.